Augmentation of depth of penetration and productivity benefits of ATIG welds using the AHP - Acharya, Samarendra; Gonda, Debasish; Das, Santanu; Bose, Dipankar; Islam, Rafikul (Creative Decisions Foundation, 2024)
ABSTRACT Weldability is a major important issue for the fabrication of different grades of stainless steel which are used in industries. Tungsten inert gas (TIG) welding is widely used in industry for accurate and precision work, but lack of penetration is observed in this process, although current and welding speed can be varied considerably to have high heat input to get deeper penetration. On the contrary, it also adversely affects mechanical properties of the weldment. To overcome this, activated flux TIG welding is often used in industry to achieve higher depth of penetration with relatively lesser heat input. In this work, activated flux TIG welding is used with input variables such as heat input, welding speed and pulse frequency. Base metal is chosen as SS 304L stainless steel. A hybrid flux mixture containing fluxes of SiO2, MnO2 and MoO3 in the ratio of 1:1:2 is used to get desired depth of penetration. Nine experimental runs are conducted to get the optimum depth of penetration. Here, heat input values are considered as 2.767 kJ/mm, 1.470 kJ/mm and 1.281 kJ/mm and pulse frequency is considered as 160 Hz, 120 Hz and 80 Hz. Welding speed varies in the range of 0.5 mm/s to 1.18 mm/s. The maximum depth of penetration of 4.42 mm is achieved with a heat input of 2.767 kJ/mm, welding speed of 0.5 mm/s and pulse frequency of 160 Hz. Reversed Marangoni effect and arc constriction effect are mainly the responsible mechanisms behind deeper penetration in ATIG welding. In this experiment, a multi criteria decision making tool, i.e. the analytical hierarchy process (AHP), is used for validating the optimum value as obtained from the experiment. It is concluded that the optimal values obtained from experiment are in good accordance with that obtained by the AHP. The outcome of the present investigation indicates applicability of ATIG welding for joining improved thickness of stainless steel flats to give enhanced productivity by reducing the number of weld passes.